Designer Micelles Accelerate Flux Through Engineered Metabolism in E. coli and Support Biocompatible Chemistry. (8th April 2016) - Wallace, Stephen; Balskus, Emily P.
Abstract: Synthetic biology has enabled the production of many value‐added chemicals via microbial fermentation. However, the problem of low product titers from recombinant pathways has limited the utility of this approach. Methods to increase metabolic flux are therefore critical to the success of metabolic engineering. Here we demonstrate that vitamin E‐derived designer micelles, originally developed for use in synthetic chemistry, are biocompatible and accelerate flux through a styrene production pathway in Escherichia coli. We show that these micelles associate non‐covalently with the bacterial outer‐membrane and that this interaction increases membrane permeability. In addition, these micelles also accommodate both heterogeneous and organic‐soluble transition metal catalysts and accelerate biocompatible cyclopropanation in vivo. Overall, this work demonstrates that these surfactants hold great promise for further application in the field of synthetic biotechnology, and for expanding the types of molecules that can be readily accessed from renewable resources via the combination of microbial fermentation and biocompatible chemistry. Abstract : Micellen und Mikroben : Von Vitamin E abgeleitete Micellen, die ursprünglich für die Verwendung als Nanoreaktoren in Wasser entwickelt wurden, sind biokompatibel und beschleunigen den Stoffwechselfluss entlang einem gentechnisch modifizierten Styrolproduktionspfad in E. coli NST74. Die mikrobenassoziierten Micellen können sowohl heterogene als auch lösliche Übergangsmetallkatalysatoren aufnehmen und katalysieren Cyclopropanierungen in vivo.